Solvent engineering for forming stonehenge-like PbI2 nano-structures towards efficient perovskite solar cells. Issue 9 (7th February 2017) - Tu, Yongguang; Wu, Jihuai; He, Xin; Guo, Panfeng; Wu, Tongyue; Luo, Hui; Liu, Quanzhen; Wang, Kai; Lin, Jianming; Huang, Miaoliang; Huang, Yunfang; Lan, Zhang; et al.
Abstract : Stonehenge-like PbI2 nanostructure, prepared via solvent substitution, provides important progress for scalable fabrication and highly efficient perovskite solar cells. Abstract : The organic–inorganic lead halide layer is a crucial factor in determining the photovoltaic performance of perovskite solar cells. Based on solvent engineering, we developed a three-step sequential coating method to prepare a high-quality CH3 NH3 PbI3 layer based on solvent (isopropanol) substitution. Stonehenge-like PbI2 nanostructures with controllable morphology and crystallinity were prepared by solvent substitution instead of the conventional annealing-treatment, affording several channels for CH3 NH3 I to penetrate into the PbI2 film due to volume expansion, and thus enabling the complete conversion from PbI2 to perovskite. In addition, the device exhibited high reproducibility by our method and achieved a high 17.78% power conversion efficiency under one-sun illumination. Furthermore, we optimized the production craft and successfully fabricated a uniform perovskite film (10 cm × 10 cm) via solvent substitution.